Cladding thickness influence on flexural strength under concentrated load of limestones - Senra, João; Dionísio, Amélia; Paneiro, Gustavo (Materials and structures, 2025)
The modern trend towards thinner and lighter cladding panels has begun to challenge the validity of current test standards. The evaluation of mechanical resistance of natural stone panels, particularly through the determination of flexural strength (FS) via EN 12372 standard, is becoming inconsistent with modern application methods. This is due to the standard requirement for a minimum sample thickness of 25 mm, which is often thicker than the actual cladding panels, leading to producers being unable to comply with the existing standard. Additionally, the heterogeneous disposition and complex structure of natural stone make FS's relationship with sample size reduction non-compliant with known size effect statistical laws. In this study, a large sample pool from six Portuguese limestones was tested to analyze the behavior of bending resistance, with sample thicknesses both above, and below the existing standard. Other physical and mechanical properties, together with petrographic compositions, were also evaluated, as previous works on the subject have demonstrated the need to comprehend their impact on the relationship between size effect and FS. Results show a tenuous inverse correlation between FS and sample thickness, with higher bending resistance in smaller samples, highlighting how measurements taken from thinner samples could result in an overestimation of FS, and the importance of physical and mechanical properties on the analysis of size effect.